Effects of efgartigimod treatment on humoral and cellular immune responses: analysis of T-cell-dependent antibody response in cynomolgus monkeys - Ornella Binazon; Mario Cocco; Daniel Thwaites; Christopher Cooper; Mahan Moshir; Peter Vanhoenacker; Dieter Defever; Ariëlla Van de Sompel; Sophie Steeland; Gwenda Pynaert; Peter Ulrichts; Judith Baumeister (Journal of Immunotoxicology)
Efgartigimod is a human IgG1 antibody Fc fragment that reduces IgG levels through neonatal Fc receptor blockade. This study evaluated whether efgartigimod affects the generation of T-cell-dependent antibodies and cellular immune responses to keyhole limpet hemocyanin (KLH) immunization in non-human primates. Cynomolgus monkeys received efgartigimod or vehicle control intravenously for 11 wk, followed by a recovery phase. KLH challenges occurred during both the dosing phase and the recovery phase. No statistically significant differences emerged in anti-KLH IgM levels between the efgartigimod and control groups. Likewise, comparable KLH-specific T cell responses were observed between groups. Anti-KLH IgG titers were lower in efgartigimod-treated animals compared with controls only after the first boost of KLH, coinciding with decreases in total IgG titers in efgartigimod-treated animals, and returned to baseline levels by the end of the recovery phase. Taken together, these results indicate that efgartigimod does not suppress T-cell-dependent antibody responses or antibody class-switching. The findings of this study are consistent with efgartigimod’s pharmacological mechanism of action and suggest that efgartigimod does not impair the generation of effective immune responses.